[PP.19.07] HYPERTENSION AND OTHER MODIFIABLE CARDIOVASCULAR RISK FACTORS IN GREECE: INTERIM ANALYSIS OF THE EMENO NATIONAL EPIDEMIOLOGICAL STUDY. (September 2016) - STERGIOU, G.S.; Margetaki, A.; Boubouchairopoulou, N.; Gavana, M.; Vantarakis, A.; Chlouverakis, G.; Chatzichristodoulou, C.; Trypsianis, G.; Voulgari, P.; Alamanos, I.; Touloumi, G.
Abstract : Objective: To date no nationwide epidemiological study of hypertension in the general population has been performed in Greece. This study evaluated the prevalence of powerful modifiable cardiovascular risk factors coexisting with hypertension in a randomly selected general population sample of adults in Greece. Design and method: The EMENO survey (National Morbidity and Risk Factors Survey) supported by the European Social Fund and national funds, is currently performed in Greece, aiming to include 6, 000 adults aged 18 years or older. It is conducted using a multi-stage stratified random sampling method, involving localities throughout the country. Interviewers and physicians made home visits, where medical history, blood sample, and automated blood pressure (BP) measurements were taken (seated position; triplicate measurements; validated electronic upper-arm BP monitors Microlife BPA100 Plus). An interim analysis of participants recruited from 03/2014 to 12/2015 was performed. Hypertension was defined as BP > 140/90 mmHg (systolic and/or diastolic) or diagnosed hypertension under treatment. The prevalence of additional modifiable cardiovascular risk factors in hypertensive subjects was evaluated with statistical methodology, taking into account the design and additional adjustments for age and sex. Results: Overall 1, 503 subjects were considered as being hypertensives. Among hypertensives, 31% reported current smoking and 21% were former smokers (43% and 13% respectively among normotensives, p < 0.001). 36.5% of hypertensives were overweight and 48% obese (37% and 24% respectively for normotensives, p < 0.001). 18.6% of hypertensives had diabetes mellitus (4% among normotensives, p < 0.001). 37% of hypertensives had LDL cholesterol >130 mg/dl treated or untreated) (32.5% in normotensives, p = 0.03). 41.5% of hypertensives had one additional cardiovascular risk factor (current smoking, obesity, diabetes mellitus, or LDL cholesterol >130 mg/dl), 28.9% had two, 7.6% three and 1% four additional risk factors (21% had no additional risk factor). Conclusions: In the adult general population in Greece, hypertension often coexists with other powerful uncontrolled modifiable cardiovascular risk factors, in higher rates than in normotensives. A national multidimensional intervention program for the prevention and management of all modifiable cardiovascular risk factors is necessary for the effective cardiovascular disease prevention.